Caribbean integration : an agenda for open regionalism. - DOOKERAN, Winston (1994)
Asserts that there is a 'reality gap' in Caribbean integration as institutions of the regional integration movement are unable to deal with the problems which people face now. Suggests a new integration with the following four (4) pillars: (1) the search for external economies of scale as opposed to internal economies of people; (2) the shaping of geographically compact economies; (3) the adoption of forward looking strategies; and, (4) the measure of the 'range' of the Caribbean economy.